Transmission lines modelling based on RLC passive and active filter design - Turki, Ahmed Qasim; Mailah, Nashiren Farzilah; Sabry, Ahmad H. (Universiti Putra Malaysia Press, 2017)
This paper presents a transmission line (TL) modelling which is based upon vector fitting algorithm and RLC passive filter design. Frequency Response Analysis (FRA) is utilised for behaviour prediction and fault diagnosis. The utilities of the measured FRA data points need to be enhanced with suitable modelling category to facilitate the modelling and analysis process. This research proposes a new method for modelling the transmission line based on a rational approximation function which can be extracted through the Vector Fitting (VF) method, based on the frequency response measured data points. A set of steps needs to be implemented to achieve this by setting up an extracted partial fraction approximation, which results from a least square RMS error via VF. Active and passive filter design circuits are used to construct the model of the Transmission line. The RLC design representation was implemented for modelling the system physically while MATLAB Simulink was used to verify the results.